A Survey of an Exposure to Extramural English Activities among EFL Undergraduate Students - Aulia Fachriyany; Banatul Murtafi'ah (EDULANGUE, 2023)
Apart from learning English in class, EFL students start learning English outside the classroom, known as Extramural English activities. This study aims to determine how often EFL undergraduate students are exposed to Extramural English activities in everyday life. It involved 153 students majoring in English Education at a private university in Indonesia who participated in the study. To garner the data, a questionnaire adapted from Barbee (2013) with a total of 34 items which consisted of three elements of language learning activities beyond the classroom, namely 1) Exposure to verbal sources of English outside the classroom, 2) Exposure to written sources of English outside the classroom, and 3) Exposure to verbal-written sources of English outside the classroom was distributed to the students. The results showed that Extramural English activities that were often carried out by the students were listening to English songs with and without lyrics, reading English content on social media, and ‘sometimes’ watching English TV series or movies with subtitles. Overall, each of these activities was carried out by students with a duration of between 4 to 5 and 5 to 7 hours each week. This research can be useful for language teachers or lecturers to motivate students to start practicing English through Extramural English language activities that students do, and for the English Education department to facilitate students' language proficiency with Extramural English activities outside of the classroom.